2022
DOI: 10.1111/ggi.14486
|View full text |Cite
|
Sign up to set email alerts
|

Assessing nutritional status in older adults requiring long‐term care: Interchangeability of bioelectrical impedance analysis and manual methods for upper arm anthropometric measurements

Abstract: In older adults, arm circumference and arm muscle circumference are common nutritional assessment tools. Bioelectrical impedance analysis devices can automatically measure arm circumference and arm muscle circumference. However, the interchangeability of the measurements made by bioelectrical impedance analysis with the actual manual measurements has not been clarified. This study examined the interchangeability of these two measurements and their relationship with sarcopenia. Methods:The interchangeability be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Fourth, a plastic adipometer was used for obtaining anthropometric measurements. Similar kits were used in previous studies [29,30], and a certain amount of evidence showed that the kits obtained accurate measurements. This kit was also used in this study; however, its accuracy and validity were not sufficient.…”
Section: Discussionmentioning
confidence: 84%
“…Fourth, a plastic adipometer was used for obtaining anthropometric measurements. Similar kits were used in previous studies [29,30], and a certain amount of evidence showed that the kits obtained accurate measurements. This kit was also used in this study; however, its accuracy and validity were not sufficient.…”
Section: Discussionmentioning
confidence: 84%
“…As a result, the cutoff value of the asymmetry index was 3.02% when the criterion value for reduced gait speed was set at <1.0 m/s. The asymmetry index of leg skeletal muscle mass can be measured automatically with BIA devices, which have the advantages of being noninvasive, having no inter‐rater error, and needing only a short measurement time 20 . Although the cutoff value of this study has high specificity, the AUC value of 0.62 is low and is not a highly accurate index for detecting a decrease in gait speed.…”
Section: Discussionmentioning
confidence: 83%
“…The asymmetry index of leg skeletal muscle mass can be measured automatically with BIA devices, which have the advantages of being noninvasive, having no inter-rater error, and needing only a short measurement time. 20 Although the cutoff value of this study has high specificity, the AUC value of 0.62 is low and is not a highly accurate index for detecting a decrease in gait speed. Further investigation, including confounding factors such as balance and leg muscle strength, [6][7][8][9] is needed to clarify the generalizability of this study and the clinical significance of leg skeletal muscle mass asymmetry.…”
Section: Discussionmentioning
confidence: 99%